Multi-Sequence MR-Based Radiomics Signature for Predicting Early Recurrence in Solitary Hepatocellular Carcinoma ≤5 cm - Wang, Leyao; Ma, Xiaohong; Feng, Bing; Wang, Shuang; Liang, Meng; Li, Dengfeng; Wang, Sicong; Zhao, Xinming (Frontiers in Oncology, 2022)
Purpose To investigate the value of radiomics features derived from preoperative multi-sequence magnetic resonance (MR) images for predicting early recurrence (ER) in patients with solitary hepatocellular carcinoma (HCC) ≤ 5 cm. Methods One hundred and ninety HCC patients were enrolled and allocated to training and validation sets (n=133:57). The clinical-radiological model was established by significant clinical risk characteristics and qualitative imaging features. The radiomics model was constructed using the least absolute shrinkage and selection operator (LASSO) logistic regression algorithm in the training set. The combined model was formed by integrating the clinical-radiological risk factors and selected radiomics features. The predictive performance was assessed by AUC. Results Arterial peritumoral hyperenhancement, non-smooth tumor margin, satellite nodules, cirrhosis, serosal invasion, and albumin showed significant correlation with ER. The AUC of the clinical-radiological model was 0.77 (95% confidence interval [CI]: 0.69–0.85) and 0.76 (95% CI: 0.64–0.88) in the training and validation sets, respectively. The radiomics model constructed using 12 radiomics features selected by LASSO regression had an AUC of 0.85 (95% CI: 0.79-0.91) and 0.84 (95% CI: 0.73-0.95) in the training and validation sets, respectively. The combined model further improved the prediction performance compared with clinical-radiological model, increasing AUC to 0.90 (95% CI: 0.85-0.95) in the training set and 0.88 (95% CI: 0.80-0.97) in the validation set (P<0.001 and P=0.012, respectively). The calibration curve fit well with the standard curve. Conclusions The predictive model incorporated the clinical-radiological risk factors and radiomics features could adequately predict the individualized ER risk in patients with solitary HCC ≤ 5 cm.